A genre analysis of abstracts in Islamic journals - Ismail, Shakirah; Ahamad Shah, Mohamed Ismail (IDOSI Publications, 2014)
The main purpose of this paper is to investigate the rhetorical structure of the abstracts of the Islamic research articles. It therefore analyzes the rhetorical structure of the abstracts of the Islamic research articles written for research papers in journals and devoted to various topics in Islam. For this purpose 100 abstracts were chosen from five Islamic journals. Specifically, the paper sought to find out if these abstracts followed or deviated from Swales’ IMRD (Introduction-Method-Results-Discussion) model. The results show that only very small percentage of the abstracts follow this model. The paper also analyzed the abstracts from a micro-structure level using the CARS (Create a Research Space) model. The results show that most of the Introduction sections of the abstracts themselves have all the moves prescribed by the CARS model. However, the number of abstracts that follow the linear order 1-2-3, was relatively small. Though most of the authors followed the rhetorical moves, they deviated in terms of its organization. Some pedagogical implications are drawn from the study.